Electronic characteristics of ultra-thin passivation layers for silicon photovoltaics - Pain, SL; Khorani, E; Niewelt, T; Wratten, A; Fajardo, GJP; Winfield, BP; Bonilla Osorio, RS; Walker, M; Piper, LFJ; Grant, NE; Murphy, JD (Wiley, 2022)
Surface passivating thin films are crucial for limiting the electrical losses during charge carrier collection in silicon photovoltaic devices. Certain dielectric coatings of more than 10 nm provide excellent surface passivation, and ultra-thin (<2 nm) dielectric layers can serve as interlayers in passivating contacts. Here, ultra-thin passivating films of SiO2, Al2O3, and HfO2 are created via plasma-enhanced atomic layer deposition and annealing. It is found that thin negatively charged HfO2 layers exhibit excellent passivation properties—exceeding those of SiO2 and Al2O3—with 0.9 nm HfO2 annealed at 450 °C providing a surface recombination velocity of 18.6 cm s−1. The passivation quality is dependent on annealing temperature and layer thickness, and optimum passivation is achieved with HfO2 layers annealed at 450 °C measured to be 2.2–3.3 nm thick which give surface recombination velocities ≤2.5 cm s−1 and J0 values of ≈14 fA cm−2. The superior passivation quality of HfO2 nanolayers makes them a promising candidate for future passivating contacts in high-efficiency silicon solar cells.